2021
DOI: 10.1080/21655979.2021.1960768
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role and clinical significance of C-reactive protein-lymphocyte ratio in colorectal cancer

Abstract: Systemic inflammatory response (SIRS) can be used as a potential prognostic marker in patients with colorectal cancer (CRC). The purpose of this study was to examine the predictive role of the C-reactive protein (CRP)-lymphocyte ratio (CLR) in the prognosis of CRC. We retrospectively analyzed the data of CRC patients who underwent surgery from 2004 to 2019. The clinicopathological characteristics and follow-up records were analyzed. According to a cutoff value of CLR, the patients were divided into the high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…According to a study which observed CLR in oral malignancy, elevated level of CLR was associated with better prognostic performance compared to other inflammatory markers in subjects with squamous cell carcinoma 11 . Similarly, Meng et al investigated CLR in patients with colorectal cancer and reported that patients with high CLR had shorter overall survival than those with low CLR levels 12 . Subsequently, Mungan et al 13 confirmed the results of Meng et al 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study which observed CLR in oral malignancy, elevated level of CLR was associated with better prognostic performance compared to other inflammatory markers in subjects with squamous cell carcinoma 11 . Similarly, Meng et al investigated CLR in patients with colorectal cancer and reported that patients with high CLR had shorter overall survival than those with low CLR levels 12 . Subsequently, Mungan et al 13 confirmed the results of Meng et al 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Meng et al investigated CLR in patients with colorectal cancer and reported that patients with high CLR had shorter overall survival than those with low CLR levels 12 . Subsequently, Mungan et al 13 confirmed the results of Meng et al 12 . In addition, prognostic value of elevated CLR has also been shown in patients with osteosarcoma 14 , cholangiocarcinoma 15 , and lung cancer 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were published in 2019-2021, 8 conducted in Japan and 2 in China.All 10 studies reported the relationship between LCR and OS, and 5 studies reported the relationship between LCR and DFS. Eight of them defined LCR as lymphocytes/C-reactive protein ratio, while the other two used Creactive protein/lymphocytes ratio (CLR) (24,29).The study by Taniai et al could be used for OS and DFS analysis after data extraction, while the study by Yongsheng Meng et al could not extract OS outcome data but could be used for analysis of pathological characteristics factors and was therefore included. The LCR threshold values ranged from 5000 to 15923.…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Since tumor patients have both inflammatory infections and immune disorders after surgery, and CRP and lymphocyte levels precisely also reflect well the inflammatory infections and immune status of patients after surgery, a series of studies on colorectal cancer patients in recent years have defined the ratio of lymphocytes to CRP as a new index and reported the correlation between LCR and prognosis of colorectal cancer (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). However, the findings of the studies are not uniform and the cut-off values for this index are not consistent; therefore, this study used Meta-analysis to objectively and systematically investigate the prognostic significance of treatment LCR levels in colorectal cancer patients and the relationship between LCR and the clinicopathological characteristics of colorectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found significant association between thyroiditis and novel inflammatory and metabolic markers, including red cell distribution width, 2 neutrophil/lymphocyte counts ratio, 3 and uric acid/HDL ratio 4 . Another novel inflammatory marker is CRP/lymphocyte count ratio (CLR) which reported to be related with pancreas malignancy, 5 cancer of the esophagus, 6 appendicitis, 7 and colorectal cancer 8 …”
Section: Introductionmentioning
confidence: 99%